PENILAIAN KINERJA DOSEN BIDANG KOMPETENSI BELAJAR MENGAJAR - Muhammad Sapruwan; Sanjaya Endra Setyawan2 (Akutansi Bisnis & Manajemen ( ABM ), 2020)
The purpose of this study is to know how to assess the performance of lecturers in teaching and learning competence, and how is the application of the weighted product method?.The criteria used are Time, Neatness, Communication, Lecture Process, Mastery of Material, Learning Evaluation. Through samples five lecturers by using the Weighted Product method, the weight is obtained with the initials of the lecturer ASR., while lecturer which has the lowest weight the initials ACP.The implications of this research study are on the basis of these weights can be used as a foundation in decision making Pelita Bangsa University's management policy actions. Lecturers who get good grades should get appreciation, while lecturers who score less will be trained. What distinguishes this research study With other research is Lecturer performance evaluation is carried out by students And followed by the weighted product method which has not been widely used in universities.